Pengembangan Perangkat Pembelajaran Bahasa Indonesia Bermodel JOSUA untuk Meningkatkan Keterampilan Menulis dan Berbicara Siswa Kelas IV Sekolah Dasar: Development of Indonesian Language Learning Toolkit with JOSUA Model to improve Writing and Speaking Skills of Grade IV Elementary School Students - Jayanto, Didit Dwi (Universitas Muhammadiyah Sidoarjo, 2018)
Inaccuracy in the use of the model will cause saturation for students and students to be passive in learning. For that need to design more innovative learning, one of the selected learning model is JOSUA learning model that can increase activity in student learning activities and student learning outcomes. This research uses 4-D development model (Four D) which develops a learning device using JOSUA model. Data analysis in this research is done by using quantitative descriptive analysis. The results of this study indicate that, the activities of students during the learning activities show active. Student responses to the JOSUA model (network, observation, simulation, and final repetition) show a good response. And there is an increase in the ability to write and speak students during the implementation of learning learning JOSUA Indonesian language (network, observation, simulation, and final repetition) can be said to increase.